Gut–brain axis and neuropsychiatric health: recent advances - Ceymi Doenyas; Gerard Clarke; Renáta Cserjési (Scientific Reports)
Abstract The gut–brain axis, a bidirectional communication pathway, permits the central nervous system (CNS) to exert influence over gastrointestinal function in response to stress, while the gut microbiota regulates the CNS via immune, neuroendocrine, and vagal pathways. Current research highlights the importance of the gut microbiota in stress-related disorders and the need for further research into the mechanisms of gut–brain communication, with potential therapeutic implications for a wide range of health conditions. This is a challenge taken on in this Scientific Reports Collection on the Gut-Brain Axis. The gut–brain axis has significant implications for neurodegenerative, psychiatric, and metabolic disorders. Recent studies have underscored the role of the gut microbiome in conditions such as Parkinson’s disease (PD), with evidence indicating that gut dysfunction and pathological features can precede motor symptoms by decades. The use of in vivo animal models has demonstrated that preformed α-synuclein fibrils (PFFs) can travel from the gut to the brain in a dosage-dependent manner, thereby supporting the “gut-first” theory in the context of PD, a theory that is explored in this Collection using in vitro approaches. There is also evidence that the gut–brain axis plays a role in obesity and machine learning algorithms may assist in differentiating between obese and overweight individuals based on their microbiota data. There is also growing interest in the role of the gut at the interface between post-traumatic stress disorder (PTSD), sleep disturbances, and irritable bowel syndrome (IBS). The studies described in this Collection support and expand on the observations from previous preclinical and clinical investigations, while also providing essential novel insights that can drive discovery into previously unexplored avenues of brain-gut-microbiome interactions in health and disease.